The war for America's soul - Gorka, Sebastian (Regnery Publishing, a division of Salem Media Group, 2019)
On one side are American patriots, dedicated to freedom under the Constitution; on the other side are leftists campaigning not just to win elections, but to radically transform the nation. In this political war for the soul of our country, America's patriots need a strategist with a blueprint for victory. Gorka shows how America's elite-- in both parties-- betrayed our heartland, sabotaged the American dream, and accepted national decline as inevitable. -- adapted from jacket